(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
STEM education is an important component for global development, many countries have invested a substantial amount of funds in the Program. Many initiatives, Programs, policies, law are formulated to increases the number of students’ enrolment and arose their interest to study STEM. In this paper, we present the comparative analysis of successful STEM education Programs in United States of America (USA), United Kingdom (UK), Japan and Australia. We explored different Programs, target groups, objectives and achievement of STEM in UK, USA, Japan and Australia. For USA, the study found that the STEM education Programs are successful but require the involvement of community elites. In UK, the STEM Education Programs are successful and it assisted the country in adding more curriculum materials and trained several personnel. In Australia, experienced a shortage of scientists and engineers and formulated policies and Programs of which some of these Programs were successful and boost the Australian STEM Education. In Japan STEM education Programs has succeeded in increasing the number of enrolment and interest in the areas of science, technology, engineering and mathematics. The stake holders, educators and government of UK, USA, Japan and Australia can use our study to easily identify areas that require improvement. As such, adapt their STEM education Programs in such a way that the STEM education Program can further be boosted.